Prevalence of hypertension and correlation with mental health in women with burning mouth syndrome: A case-control study - Canfora, Federica; Calabria, Elena; Pecoraro, Giuseppe; Leuci, Stefania; Coppola, Noemi; Mazzaccara, Cristina; Spirito, Francesca; Aria, Massimo; D'Aniello, Luca; Mignogna, Michele Davide; Adamo, Daniela (Frontiers in Cardiovascular Medicine, 2023)
Background: The relationship between hypertension (HTN) and chronic pain is still a matter of debate and its prevalence in patients with Burning Mouth Syndrome (BMS) has never been evaluated. The aim of the study has been to assess the prevalence of HTN in women with BMS and to evaluate its relationship with potential predictors such as risk factors for cardiovascular diseases, pain and mental health status analyzing differences with healthy women. Methods: 250 women with BMS (WBMS) were prospectively recruited and compared with an equal number of healthy women (HW) matched for age. Education, Body Mass Index, smoke and alcohol consumption, intensity and quality of pain, and psychological profile, were further investigated to find potential predictors of HTN. Specifically, pain assessment [the Numeric Rating scale (NRS), Short-Form McGill Pain Questionnaire (SF-MPQ) and psychological assessment [Hamilton Rating Scale for Depression and Anxiety (HAM-D and HAM-A), Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS)] were administered. Results: HTN was found in 128 (51.2%) of WBMS and in 76 (30.4%) HW (p-value<0.001**). The scores of the NRS, SF-MPQ, HAM-D, HAM-A PSQI, were statistically significantly higher in the WBMS than the HW (p < 0.001**). A strongly linear correlation between HTN and employment status, systemic diseases, and education level (p-value<0.001**) was found in WBMS; while HTN was strongly correlated with employment status, hypercholesterolemia, systemic diseases, and drug consumption in HW (p-value<0.001**). No statistically significant correlation was found between HTN with pain, anxiety, depression, and sleep disturbances. Conclusion: These results suggest that WBMS showed a higher prevalence of HTN compared with controls. Unemployed WBMS with lower education and other systemic comorbidities are at increased risk to develop HTN. HTN is associated with alteration in the vascular structure and function of the brain and these processes accelerate the brain ageing which contributes to a reduction in intracortical connectivity affecting the modulatory system of control of pain in BMS patients, independently of their mental health assessment. Predictors that may underlie this association remains unclear taking into account the differences found in HW, and should be furtherly elucidated.